Desafios da cadeia produtiva da meliponicultura no interior da Amazônia: produção de mel na Comunidade Palmari, Atalaia do Norte, Amazonas, Brasil. - Ribeiro, Gregoria Coelho (Brasil, 2023)
The creation of stingless bees called meliponiculture has been gaining space in the market, as it presents a natural product from sustainable breeding without the possible degradation of the environment, especially when this production chain is inserted in a biome as important as the Amazon forest. But there are some challenges, honey production has not been following the high market demand, so it was possible to investigate which management factors affect the productivity of the beekeeper in the interior of the Amazon region. This study aims to describe the meliponiculture supply chain focusing on the production processes of a local experience, from the Palmari community, Atalaia do Norte, Amazonas, Brazil. The methodological procedures that guide the research are of a descriptive nature, the data were obtained through a participant research with the meliponicultor throughout the production process, and a thematic interview with the IDAM agent for data collection at a regional level, the data were categorized according to Michael Porter's supply chain (1985) in order to identify all the links related to the honey production chain. As a result of the research, it was possible to describe all the links that make up the supply chain in the Palmari Community, from the acquisition of raw materials to the delivery of the product to the final consumer. The existing barriers in production are the lack of time to dedicate exclusively to production and the devaluation of the price of the final product, in addition to the feasibility of creating an Association that can support beekeepers in Alto Solimões.